Evaluation of the dentin-pulp complex after cavity preparation with ultrasonic diamond tip - Monti Lima, L.; Baffi Diniz, M.; Aparecida Seccani Galassi, M.; Toledo de Oliveira Ramalho, L.; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (My University, 2011)
The aim of this paper was to compare the dentin-pulp complex response to cavity preparation in human teeth using ultrasonic chemical vapor deposition (CVD) diamond tip and high-speed diamond bur. Class V buccal cavities were randomly prepared in 40 premolars from 14 patients aged 11 to 15 years. The cutting time was recorded and the cavities had the axial walls protected with gutta-percha and were filled with glass ionomer cement. The teeth were extracted at intervals of 0, 5, 10 and 20 days, and were decalcified, sectioned and stained by Hematoxylin & Eosin, Masson's Trichrome and Brown & Brenn techniques. The inflammatory response and cell disorganization were blindly evaluated by two examiners. The remaining dentin thickness (RDT) was measured by a linear scale using computer software. Statistical analysis by one-way ANOVA showed no statistically significant difference (P≤0.05) among the cavities prepared with either type of instrument, with mean RDT of 1132.50 mm. Cutting time and the pulp-dentin complex responses were analyzed statistically by Kruskal-Wallis and Dunn tests (P≤0.05). The ultrasonic CVD diamond tip took 5 times longer to prepare the cavities and there were no typical inflammatory pulp responses in cavities prepared with either type of cutting instrument, only mild to moderate cell disorganization was present. Even taking longer to cut the dental substrate, the ultrasonic CVD diamond tip produced similar pulp response compared to the conventional high-speed diamond bur.
Keywords: diamond; glass ionomer; gutta percha; adolescent; child; clinical trial; comparative study; controlled clinical trial; controlled study; dental equipment; dental surgery; dentin; human; inflammation; instrumentation; odontometry; premolar tooth; single blind procedure; staining; time; tooth extraction; tooth pulp; ultrasound; ultrastructure; Adolescent; Bicuspid; Child; Dental Cavity Preparation; Dental High-Speed Equipment; Dental Pulp Cavity; Dentin; Diamond; Glass Ionomer Cements; Gutta-Percha; Humans; Inflammation; Odontometry; Single-Blind Method; Staining and Labeling; Time Factors; Tooth Extraction; Ultrasonics